Pengembagan Kapasitas Kelompok Tani Hortikultura di Dusun Telaga Kodok Kecamatan Leihitu Kabupaten Maluku Tengah - Abut Ipa; Melvis E. Tahitu; Jeter D. Siwalette (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the capacity level of horticultural farmer groups in talaga kodok hamlet, Leihitu district, Central Maluku regency and for what factors are related to the capacity level of horticultural farmer groups in talaga kodok hamlet, Leihitu district, Central Maluku regency. This research will be conducted at the Horticultural Farmer Group of Telaga Kodok Hamlet, Leihitu District, Central Maluku Regency for 1 month, from October 2022 – November 2022. The data collected by observation and interviews were then analyzed with qualitative descriptive analysis. The farmer group in telaga kodok hamlet consists of ten registered farmer groups but eight active farmer groups, some of which changed group names and changed groups, because the existence of farmer groups is only a formality to make it easier to get help from the government and other parties. The capacity level of farmer groups in telaga toad hamlet based on routine activities and task distribution obtained an average score of 2.60 with high categories, adequate facilitation obtained an average score of 1.33 with low categories, farming experience obtained an average score of 2.30 with high categories, group norms and rules obtained an average score of 2.16 with high categories and group achievements obtained an average score of 1.23 with high categories. Factors that affect the level of capacity of farmer groups in telaga kodok hamlet, there are 2 factors, namely internal factors and external factors, internal factors obtained an average score of 2.90 with high categories and external factors obtained an average score of 1.31 with low categories.